Binary Log Analysis on MySQL to Help Investigation Process Against Database Privillege Attacks - Siti Rokhmah; Ihsan Cahyo Utomo (International Journal of Computer and Information System (IJCIS), 2020)
Abstract—Database is an important part in managing information, because a database is a collection of data that is processed to produce information. because of the importance of the database, many crimes are directed to attack the database, both attacks against access rights or attacks against the data itself. My SQL is a Database Management System (DBMS) that provides several facilities, one of which is the logging facility. Binary Log is a type of database log in the form of binary digits that contains some information including the record of the time of the transaction, the user who made the transaction and the order in the transaction. With the Binary Log, it can be seen when the transaction occurred, who made the transaction and what transaction occurred in the database. The recording of transactions in the Binary Log can be used as one way to carry out an investigation process in the event of an attack on the database. In this study the focus is on analyzing transaction records in binary logs, namely when, who, dam and what information can be taken from the Binary Log. The output of this research is a table of binary log investigation results and its relation to database attacks.